Impossible Mourning: HIV/AIDS and Visuality After Apartheid - Thomas, Kylie (University Press Copublishing Division, 2013)
Impossible Mourning argues that while the HIV/AIDS epidemic has figured largely in public discourse in South Africa over the last ten years, particularly in debates about governance and constitutional rights post-apartheid, the experiences of people living with HIV for the most part remain invisible and the multiple losses due to AIDS have gone publicly unmourned. This profound fact is at the center of this book which explores the significance of the disavowal of AIDS-death in relation to violence, death, and mourning under apartheid. Impossible Mourning shows how in spite of the magnitude of the epidemic and as a result of the stigma and discrimination that has largely characterized both national and personal responses to the epidemic, spaces for the expression of collective mourning have been few. This book engages with multiple forms of visual representation that work variously to compound, undo, and complicate the politics of loss. Drawing on work Thomas did in art and narrative support groups while working with people living with HIV/AIDS in Khayelitsha, a township outside of the city of Cape Town this book also includes analyses of the work of South African visual artists and photographers Jane Alexander, Gille de Vlieg, Jillian Edelstein, Pieter Hugo, Ezrom Legae, Gideon Mendel, Zanele Muholi, Sam Nhlengethwa, Paul Stopforth, and Diane Victor.